Hamlet: plea for a measure of normality. Issue 2 (2nd July 2016) - Zachrisson, Anders
ABSTRACT: The author first considers issues in psychoanalytic interpretations of literary characters, especially the question of treating the character as fiction (the aesthetic illusion) or as a real person. The position he adopts is to interpret Hamlet as a potential person, created by Shakespeare and an expression of Shakespeare's actual – and intuitive – view of man. With a synopsis of the tragedy and the context of its creation as background, the author then reflects on questions concerning the play. How does Shakespeare present the characters? Is Hamlet's madness pretended or real? Which conflicts does he handle in the course of the play? Has Oedipal dynamics a role as motivational factor in his mind? Hamlet is irrational, impulsive, emotional, inhibited, brooding, suspicious, revengeful, condemning and much more. But, in the view of the author, he is all this in a human, 'normal' way. There is nothing convincingly pathological or constricted in his character. 'Un-normal' is his intelligence and his wit. Hamlet – an intelligent, reflected, resourceful prince in late Renaissance – who has wrestle with a madhouse of political intrigues, family murders and deceitful friends. Hamlet in Shakespeare's text – a fairly normal person in quite a mad world.